A case of mucopolysaccharidosis type VI in a polish family. Importance of genetic testing and genotype-phenotype relationship in the diagnosis of mucopolysaccharidosis - Zapała, Barbara; Chmura, Olaf; Ciałowicz, Urszula; Solnica, Bogdan; Krajewska-Włodarczyk, Magdalena; Żuber, Zbigniew (Molecular genetics and metabolism reports, 2020)
Mucopolysaccharidosis type VI (MPS VI) is a rare, autosomal recessive lysosomal storage disorder caused by deficient enzymatic activity of N-acetyl galactosamine-4-sulphatase, which is caused by mutations in the arylsulphatase B (ARSB) gene. To date, 163 different types of mutations in the ARSB have been reported. However, the full mutation spectrum in the MPS VI phenotype is still not known. The aim of this study was to perform molecular testing of the ARSB gene in the patient and his family members to confirm MPS VI. Molecular characterisation of the ARSB gene was performed using Sanger sequencing. We studied a child suspected of having MPS VI and 16 other relatives. We identified a C-to-T transition resulting in an exchange of the Arg codon 160 for a premature stop codon (R160*, in exon 2). The transition was in CpG dinucleotides. The study provided some insights into the genotype-phenotype relationship in MPS VI and the importance of genetic testing when diagnosing MPS, which is not a mandatory test for the diagnosis and only very occasionally performed. Additionally, we present here the history of a family with confirmed MPS VI, which is extremely rare especially in south-eastern Poland. What is more, the position where the mutation is located is very interesting because it is the region of CpG, which is the site of the methylation process. Thus, this opens the possibility of a new approach indicating the involvement of an epigenetic mechanism that should be examined in the context of the pathomechanism of MPS.